MENDESAIN PROFIL GURU BERKARAKTER CERDAS - Susilo Rahardjo (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2017)
Teacher is the main factor in education. The teacher quality improvement is compulsory to be done in the internalization of character building. This is only can be done if teacher as a model of the students can show the good characterized personality. This article aimed to explore about how important to design teacher training to enhance teacher with smart personality.